The impact of self-efficacy and math anxiety on the mathematical communication ability of 7-grade students - Hanub, Aan Julia; Istiqomah, Istiqomah; Kusumaningrum, Betty; Poort, Elang Amadeus (UNION : Jurnal Ilmiah Pendidikan Matematika, 2023)
The primary aim of this study is to assess the influence of self-efficacy and math anxiety on the proficiency of mathematical communication among Class VII students enrolled in State Junior High Schools within the Depok District. The research methodology is quantitative, employing an ex-post facto correlational descriptive approach. The study encompasses the entire population of Class VII students across all State Junior High Schools within the Depok District, with a sample size of 190 students selected through cluster random sampling. Data collection involves employing questionnaires to gauge students' self-efficacy and math anxiety levels, alongside descriptive tests to evaluate their aptitude in mathematical communication. Preceding the analysis, preliminary tests are conducted to assess linearity and multicollinearity. The data analysis procedure encompasses multiple regression analysis and t and F tests to ascertain both individual and collective impacts. The findings reveal the absence of a discernible impact from self-efficacy and math anxiety on the mathematical communication skills of Class VII students in State Junior High Schools in the Depok District. For subsequent researchers, it is recommended to carefully consider the construction of questionnaire statements to ensure their comprehensibility among students.